Design Thinking to Solve Problems with the Selection of Metrics in Software Quality - Sutta Gonzales, Eduardo Armando (2022)
In this article, the Design Thinking technique will be used to solve and evaluate the problem of the selection of software quality metrics, considering some techniques for the collection of ideas that can support the development of a solution purpose to the problem that in this case is the quality assurance based on the evaluation metrics defined in the current known standards. All this is possible thanks to the support of web tools that provide templates to cover the phases of Design Thinking. The details of the phases are also made starting with the Empathizing phase followed by Define, Devise, Prototype, Test and finally arriving at the results and conclusions found after the whole design thinking process. The results are expected to help build quality software and be used in a real project and in its different stages making the software successful in the market.